Efeito de mecanismos rotativos auxiliares à haste sulcadora na semeadura direta de soja e milho - Becker, Rafael Sobroza (2024)
The present thesis assumes that the loosening of the furrow line formed by the use of the furrow opener type shank is essential for maintaining the principles of the No-Till Agriculture (SPD) system. However, there is a noticeable absence of tests applied to active components of seedfertilizer drills for straw and soil management. Therefore, studies and developments of auxiliary mechanisms that provide better conditions for vertical and longitudinal seed allocation are necessary, identifying and measuring the operational behavior of shanks associated with auxiliary rotary mechanisms. Thus, the objective of the study was to evaluate the no-till seeding system for soybeans and corn, using different mechanisms and adjustments associated with the fertilizer furrow opener to reduce the non-uniformity of seed depth allocation, emergence speed, and longitudinal plant distribution practiced by seed-fertilizer drills operating in different types of soil. The study was conducted in 2 experiments implemented on agricultural properties located in two different regions of the state of Rio Grande do Sul, during the direct seeding of commercial crops of soybeans and corn in the agricultural year 2022/2023. Each experiment was arranged in a Randomized Complete Block Design, in a two-factor arrangement with an additional 2x4 + 1 treatment, with 3 blocks, totaling 9 treatments and 27 experimental units. The first factor consisted of furrow-forming mechanisms, with 2 levels, the first being the furrow opener associated with double disk A, and the second being the furrow opener associated with double disk B. The flat double disks consisted of a pair of narrow-tread disks mounted on axles with tilt adjustment. Additionally, the factorial experiment received an additional treatment, corresponding to the control or witness treatment, composed of the use of the furrow opener without the addition of double disks. The second factor consisted of adjusting the vertical angle of attack of the flat double disks, with 4 levels. The response variables were the measurement of the straw permanence index in the soil, seed allocation depth, emergence speed, and longitudinal plant distribution. The data were subjected to the Shapiro-Wilk test to check for normality and the Bartlett test to check for variance homogeneity, as well as analysis of variance (ANOVA) and verification of the significance of factors through the F-test. The use of double disks associated with the furrow opener is efficient in improving seeding in terms of straw permanence index, plant emergence speed, seed depth allocation, and longitudinal plant distribution in the operation of no-till seeding of soybeans and corn.